2010
DOI: 10.1111/j.1748-1716.2010.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early exercise on brain damage and recovery after focal cerebral infarction in rats

Abstract: AimExercise can be used to enhance neuroplasticity and facilitate motor recovery after a stroke in rats. We investigated whether treadmill running could reduce brain damage and enhance the expression of midkine (MK) and nerve growth factor (NGF), increase angiogenesis and decrease the expression of caspase-3.MethodsSeventy-seven Wistar rats were split into three experimental groups (ischaemia-control: 36, ischaemia-exercise: 36, sham-exercise: 5). Stroke was induced by 90-min left middle cerebral artery occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 54 publications
3
51
0
1
Order By: Relevance
“…Augmented PECAM-1 immunoreactivity in and around ischemic lesions, reflective of higher blood vessel density, has been found particularly between 2 and 14 days after stroke in different rodent models (21,22,24). Furthermore, PECAM-1 expression in post-stroke brain tissue has been shown to increase in response to angiogenesis-stimulating exercise (22), and to decrease after administration of an angiogenesis inhibitor (23)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Augmented PECAM-1 immunoreactivity in and around ischemic lesions, reflective of higher blood vessel density, has been found particularly between 2 and 14 days after stroke in different rodent models (21,22,24). Furthermore, PECAM-1 expression in post-stroke brain tissue has been shown to increase in response to angiogenesis-stimulating exercise (22), and to decrease after administration of an angiogenesis inhibitor (23)…”
Section: Discussionmentioning
confidence: 97%
“…PECAM-1 has been frequently applied as an endothelial marker in tissues, including assessments of changes in vascularization after experimental stroke (22)(23)(24)(25). Augmented PECAM-1 immunoreactivity in and around ischemic lesions, reflective of higher blood vessel density, has been found particularly between 2 and 14 days after stroke in different rodent models (21,22,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treadmill exercise is a forced exercise in animal studies which may induce stress, and stress may have negative effect on rats' recovery, since stress has been found to affect structural plasticity of the hippocampus in two forms [11]: repeated stress causes atrophy of dendrites in the CA3 region, and both acute and chronic stress suppresses neurogenesis of dentate gyrus granule neurons. On the contrary, other researchers believed treadmill exercise training can protect neurons [12], [13]. For example, Hayes' study showed that treadmill exercise assisted neuroprotection and it was proposed that there is something else brought by treadmill training but not the stress inducing such neuroprotection result [14].…”
Section: Introductionmentioning
confidence: 89%
“…They found that early treadmill training (started 24h post MCAo/r surgery, 30min per day, 5 days a week with a speed of 20m/min and 0° slope, and rats experienced one-week training and another one-week resting, and then were sacrificed) had significant effects in reducing brain infarct volume compared with spontaneous recovery. In Matsuda's study [13], researchers found that treadmill exercise starting from 24h after MCAo/r surgery for 28 consecutive days reduced neurological deficits and infarct volume in Wister rats weighing 220-260g. Even though the protocols (one-week training plus one-week resting, 4-week training, and this one-week consecutive training), the species (SD rats or Wister rats) or weights are different between theirs and ours, all results supported that treadmill training can facilitate post-stroke motor function recovery and provide neuroprotection in rats.…”
Section: Discussionmentioning
confidence: 99%